Policy Implementation of Health Coverage for Indonesian Migrant Workers - Hartono, Risky Kusuma; Hidayat, Budi; Pujiyanto, Pujiyanto (UI Scholars Hub, 2016)
The purpose of this research is to analyze the policy implementation of health coverage for TKI. This research uses a qualitative method with in-depth interview. The framework of this research consists of the aspect of the advisable policy, the implementation factors, and the schematic representation of the problem by using SWOT. The result of this research is the health insurance owned by TKI comes from TKI insurance, the membership of JKN, and insurance during their employment abroad. TKI insurance policy is the instruction of Law No. 39 of 2004 which regulates the obligation of the ownership of the social security and or insurance policy for TKI. However, TKI insurance has not been involved with the social aspect because the agency commercializes the coverage of TKI and it is not included a social security. The change of consortium may have decreased the ratio of claim’s values to the annual premium which is attributable to the decreasing complaint cases from TKI. In the implementation, TKI insurance has been assisted by a lot of agencies. However, the bilateral cooperation related to the coordination of health coverage among countries has not been maximized. This research concludes that the coverage of health insurance for TKI is still lower (curative) and the government's attempt to integrate the social security for TKI is important. The researcher suggests the government should comprehensively implement the health coverage for TKI by incorporating the principle of promotion and prevention.